A new active NaVMoO6 cathode material for rechargeable Li ion batteries. (10th March 2021) - Huang, Chunmao; Liu, Shenghong; Wang, Yang; Feng, Jingjie; Zhao, Yanming
Abstract: Brannerite-type NaVMoO6 with vanadium (V 5+ ) and molybdenum (Mo 6+ ) elements in the highest valence states is synthesized by a sol-gel method using Na2 CO3, NH4 VO3, MoO3 and citric acid reagents. The results of X-ray diffraction (XRD) with Rietveld refinement and X-ray photoelectron spectroscopy (XPS) show that the obtained NaVMoO6 sample is single-phase. Novel electrode material (NaVMoO6 ) with layered structure is first utilized as cathode material for lithium ion batteries (LIBs). The NaVMoO6 electrode delivers reversible specific capacity of 126.4 mA h g −1 at 5 mA g −1 after 50 cycles. The stable structure of NaVMoO6 is corroborated by ex-situ XRD, suggesting that this material is considered as a prospective cathode for LIBs. This studying enriches the possibilities of molybdenum-based materials as cathodes for LIBs.